Pemberdayaan UMKM Produk Mahar Melalui Pelatihan Digitalisasi Pemasaran Pada Rona Creation Nganjuk - Chamid, Nur; Yuliani, Yuliani; Amalia, Fransisca; Putri, Oktaria Ardhika (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This study discusses how to use social media in the midst of the Covid-19 pandemic as a marketing medium for Rona Creation's UMKM "dowry products" in Pacekulon Village. The purpose of the research is to introduce Rona Creation's "dowry product" to the wider community through the use of social media as a marketing medium so as to increase the potential of a larger market. The method used in this study is Asset Based Community Development (ABCD). The implementation of the research is by socializing the importance of social media, with the implementation of digitalization socialization to UMKM actors Rona Creations can make them aware of the importance of social media technology so that UMKM actors Rona Creations Creation can market its products following technological developments.